Bridging Knowledge and Fear: Citizen Science in Enhancing Herpetofauna Literacy, Identification Skills, and Reduced Fear - Samitra, Dian; Widiya, Mareta (Jurnal Pendidikan MIPA, 2025)
Species literacy and species identification skills are important to protect diversity and are issues in Sustainable Development Education. Fear of animals, especially herpetofauna, makes students avoid them and makes it difficult to study them. Based to the literature study, citizen science has the potential to solve this problem. This study aims to determine the impact of citizen science on species literacy, species identification skill, and fear of herpetofauna. This study included 44 biology education students from PGRI Silampari University who were studying Vertebrate Zoology classes. The data on species literacy was obtained using essay questions. Reports provided information on species identification skills. A questionnaire was used to collect fear data on the herpetofauna. The instrument used was declared valid and reliable. Species identification ability data was analyzed based on species resulting from citizen science activities. Species literacy data were analyzed descriptively and using the Wilcoxon Signed Rank test. Literacy increase data is calculated using the N-Gain Score. The results obtained show that 1) Species literacy data after the Wilcoxon test obtained sig. <0.05. The N-gain analysis obtained was 0.72 in the high category. 2) The herpetofauna identification data was 71.23%, indicating that students skills are passable in identifying species. The results of citizen Science activities showed that a maximum of 17 species were caught and a minimum of 6 species; 3) The Wilcoxon test revealed a significant difference in fear of herpetofauna (sig. < 0.05). Therefore, it can be concluded that Citizen Science significantly increases students' species literacy, identification abilities and reducing students' fear of herpetofauna.        Keywords: citizen science, species literacy, species identification skill, herpetofauna.